2016
DOI: 10.1182/blood-2015-05-644872
|View full text |Cite|
|
Sign up to set email alerts
|

ATR inhibition induces synthetic lethality and overcomes chemoresistance in TP53- or ATM-defective chronic lymphocytic leukemia cells

Abstract: Key Points• ATR inhibition is synthetically lethal to TP53-or ATMdefective CLL cells.• ATR targeting induces selective cytotoxicity and chemosensitization in TP53-or ATM-defective CLL cells in vitro and in vivo.TP53 and ataxia telangiectasia mutated (ATM) defects are associated with genomic instability, clonal evolution, and chemoresistance in chronic lymphocytic leukemia (CLL). Currently, therapies capable of providing durable remissions in relapsed/ refractory TP53-or ATM-defective CLL are lacking. Ataxia te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
192
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(209 citation statements)
references
References 71 publications
16
192
1
Order By: Relevance
“…This synthetic lethal effect is also observed in xenograft models of p53-or ATM-defective primary CLL, where AZD6738 treatment not only significantly reduces tumor load [44], but also overcomes resistance to chemotherapeutics used in the first-line treatment of CLL such as chlorambucil, fludarabine, or bendamustine. Collectively, these results support the combined use of ATR inhibitor with a range of existing therapeutic agents for CLL.…”
Section: The Essential Function Of Ddr In the Maintenance Of Hscsmentioning
confidence: 83%
See 1 more Smart Citation
“…This synthetic lethal effect is also observed in xenograft models of p53-or ATM-defective primary CLL, where AZD6738 treatment not only significantly reduces tumor load [44], but also overcomes resistance to chemotherapeutics used in the first-line treatment of CLL such as chlorambucil, fludarabine, or bendamustine. Collectively, these results support the combined use of ATR inhibitor with a range of existing therapeutic agents for CLL.…”
Section: The Essential Function Of Ddr In the Maintenance Of Hscsmentioning
confidence: 83%
“…Recent in vitro studies have shown that pharmacologic inhibition of ATR in p53-or ATM-defective CLL cells selectively induces replication fork stalls, accumulation of unrepaired DNA damage, and mitotic cell death [43,44]. This synthetic lethal effect is also observed in xenograft models of p53-or ATM-defective primary CLL, where AZD6738 treatment not only significantly reduces tumor load [44], but also overcomes resistance to chemotherapeutics used in the first-line treatment of CLL such as chlorambucil, fludarabine, or bendamustine.…”
Section: The Essential Function Of Ddr In the Maintenance Of Hscsmentioning
confidence: 99%
“…In preclinical models of hematologic malignancies, cells that lack ATM (e.g., due to 11q deletions) or have defects in p53 signaling were particularly vulnerable to the ATR inhibitor AZD6738. Treatment with AZD6738 increased replication initiation and fork stalling, resulting in RS and DNA damage that likely contributed to selective cytotoxicity in cells with p53 and/or ATM defects (64). In parallel, in a phase I trial with the ATR inhibitor VX970 and carboplatin, a patient with colorectal cancer and ATM loss achieved a complete response (65).…”
Section: Strategies For Clinical Development: Past and Presentmentioning
confidence: 99%
“…Notably, ATM-deficient lung cancer xenografts were particularly sensitive to a combination of cisplatin and (78). In studies with primary leukemic cells from patients with chronic lymphocytic leukemia, AZD6738 had superior cytotoxicity in CLL cells induced to divide (79), and in ATM-or TP53-mutated CLL cells (80). A first-in-man study was initiated in ATM-deficient non-Hodgkin lymphoma, and a subsequent study will be initiated in combination with radiotherapy for the treatment of patients with head and neck cancer, based on evidence that ATR inhibition can sensitize ATM-deficient cancer cells to ionizing radiation (68,81).…”
Section: Targeting Atrmentioning
confidence: 99%